Improving The Students’ Vocabulary Mastery By Using Fly Swatter Game At The Tenth Grade Of Sma Negeri 1 Gunungsitoli Idanoi In 2022/2023 - Audian Meria Yanti Laoli; Kristof Martin Efori Telaumbanua; Elwin Piarawan Zebua; Yaredi Waruwu (Departement of Mathematics Education, 2023)
In learning English, the first thing that must be learned is vocabulary. This means that learning vocabulary is very important, especially for students in high school. Based on the researcher observations at the tenth grade, the technique used in learning is monotonous which makes students tend to get bored so that student participation in class is lacking. The vocabulary problem must be solved, because it can make it difficult for students to continue to the next level or class. Also students may have low motivation in learning English because they feel English is difficult. The objectives of the researcher is to improve students vocabulary mastery by using Fly Swatter Game. Based on the identification of the problems above, the researcher wants to overcome the problems of the students in English vocabulary mastery. In this research, the researcher use Classroom Action Research as a research design that was held in two cycles. The subject of the research was the students of X-IPS 1 which consist of 23 students. In this research, the instrument are evaluation sheet and observation sheet. From the result of each cycle, it shown that; in Cycle I, there was not students’ value which could be classified in “good level”, there were 3 students’ value (13,04%) in “good level”, there were 3 students’(13,04%) in “enough level”, there were 7 students’ value (30,43%)in “less level”, there was 10 students’ value (43,47%) in “fail level”. The average of the students’ value was 46,3. It showed that Cycle I was not successful, so this research has continued to the next cycle after revising the plan based on the weaknesses in cycle I. The result of Cycle II research showed that there was not students’ (0%) values classified in the “enough“, “less” and “fail level.” There were 8 students’ values (34,77%) in the “good level”, and 15 students’ values (65,21%) in the “very good level”. The average value of the students’ was 86,5. Based on the result above the researcher concludes that Fly Swatter Game could be done in teaching vocabulary and could improve the students’ ability in mastering vocabulary.